Estimation of sucrose solution saturation to assess the drought resistance of alfalfa varieties in the conditions of the Saratov Trans-Volga region - T. N. Popova (Зерновое хозяйство России)
For normal alfalfa growth and development, a high supply of moisture is of great importance. The most stable fodder productivity is obtained on irrigated and floodplain lands. Though, water excess can also have a negative effect, especially on seed productivity. Alfalfa seeds can absorb large amounts of water, no less than their dry matter weight. Under a soil moisture shortage, low soil temperature and deep seeding, sprout emergence slows down.   The main purpose of the current work was to analyze the effect of sucrose solutions of various saturations on seed germination and determine the desired saturation, which would be best used to estimate the relative drought resistance of alfalfa varieties under conditions of osmotic stress.   The work was carried out at the “Ershovskaya ESIA, the branch of the FSBSI FARC of the South-East” in 2021–2022. There has been conducted trials to consider the effect of different solution saturations on the germination of alfalfa seeds of the varieties ‘Artemida’, ‘Yuzen’, ‘Virineya’, ‘Natali’ and ‘Sirena’. As a result of the study, there was shown that, depending on the varieties and saturation of the solution, seed germination varied from 4 to 100 %. The variety ‘Yuzen’ showed maximum seed germination of 75.2 % and a minimal decrease in germination with increasing osmotic pressure relative to other varieties. At the highest sucrose solution saturation (16.6 %), the best figures were produced by the varieties ‘Artemida’ and ‘Virineya’. Our trial has identified that to determine the relative drought resistance of alfalfa varieties, it was most effective to use sucrose solutions with a concentration of 7.4 and 16.6% for a more reliable result.